보건의료 빅데이터를 활용한 의료장비 및 방사선사 인력 현황 연구 : 2020-2021년 자료를 기준으로 - 장현철; Hyon-chol Jang (한국방사선학회 논문지, 2021)
4차 산업혁명 시대에 진입하면서 방사선 의료 기술 개발의 혁신 및 고도화에 따라 방사선사의 업무 범위는 더욱더 확대될 것으로 판단된다. 본 연구에서는 의료장비 및 방사선사 인력 현황을 파악하여 4차 산업 혁명시대 변화에 있어 방사선 의료기술분야 인재 양성 계획, 진로 및 취업 상담에 기초자료를 제공하고자 하였다. 보건의료 빅데이터를 이용하여 2020년부터 2분기 자료와 2021년 2분기 자료를 통해 분석하였다. 연구결과 2020년 대비 2021년 종별 의료장비 현황 비교 결과 C-Arm X-선 검사 장비가 6,638대로 5.83% 가장 높게 증가하였으며, 다음 순으로 MRI 검사 장비 1,811대 5.29%, 혈관조영 검사 장비 725대 5.22%, 일반 X-선 검사 장비 21,557대 3.99%, CT 검사 장비 2,136대 3.03%, 유방 검사 장비 3,425대 3.00% 증가하였다. 2020년 대비 2021년 전체 방사선사 인력 현황 비교 결과 29,038명으로 2.73% 증가하였다. 지역별 방사선사 인력 현황 비교 결과 경기 지역에서 5.96%로 가장 높게 증가하였으며, 다음순으로 강원 지역 5.66%, 충남 지역 3.81% 증가하였다. 의료장비 및 방사선사 인력이 증가하는 상황에서 대학에서는 4차 산업혁명 시대 의료 방사선 기술영역에서 적용할 수 있는 맞춤형 인공지능 및 빅데이터에 관한 이해 및 활용과 관련된 교과목 개발을 통한 전문적 지식과 실무역량을 갖춘 방사선사 양성이 필요하며, 협회 차원에서는 새로운 일자리 창출 및 취업 향상을 위한 적극적인 정책이 필요할 것으로 생각된다. As we enter the era of the 4th industrial revolution, it is judged that the scope of work of radiologists will be further expanded according to the innovation and advancement of radiation medical technology development. In this study, the current status of medical equipment and radiology technicians was identified, and basic data were provided for the plan for nurturing talents in the field of radiation medical technology in the era of the 4th industrial revolution, as well as career and employment counseling. Data from the second quarter of 2020 and the second quarter of 2021 were analyzed using health and medical big data. As a result of comparing the status of medical equipment by type in 2021 compared to 2020, C-Arm X-ray examination equipment increased by 5.83% to 6,638 units, followed by MRI examination equipment 1,811 units 5.29%, and angiography equipment 725 units 5.22%, general X-ray examination equipment 21,557 units increased 3.99%, CT examination equipment 2,136 units 3.03%, and breast examination equipment 3,425 units increased 3.00%. As a result of a comparison of the total number of radiologists in 2021 compared to 2020, the number was 29,038, an increase of 2.73%. As a result of comparing the status of radiographers by region, the increase was highest in the Gyeonggi region with 5.96%, followed by the Gangwon region with a 5.66% increase and the Chungnam region with a 3.81% increase. In a situation where the number of medical equipment and radiologist manpower is increasing, universities are developing specialized knowledge and practical competency through subject development related to the understanding and utilization of customized artificial intelligence and big data that can be applied in the medical radiation technology field in the era of the 4th industrial revolution. It is necessary to nurture qualified radiographers, and at the level of the association, it is thought that active policies are needed to create new jobs and improve employment.